SISTEM EKONOMI HUMANISTIK VERSUS EKONOMI BEBAS - Prawiro, Atmo (An Nawawi, 2021)
The debate of the world economic system that began post-cold war until today can be said victory is in the capitalistic system that uses the free market as one of its characteristics. The collapse of Unisovyet signifies the power of capitalistic economy as the ruler of the world economy. Because almost the countries in the world apply this system. In some countries the world is actually a lot of economic system that is used, but the fact that most of the capitalistic world that dominate it. Similarly, Indonesia is also a free market capitalistic system, although Indonesia in its constitution uses Pancasila economy (humanistic economy) which loves togetherness (ukhwah) and religious ruhs. This research uses descriptive analysis approach, with the sources used are published books and journals. The author finds that the humanist economic system in terms of the above concept belongs to the commonalities of Islamic values, even this humanist economy provides for mutuality, mutual help and high spiritual dimension, and this differs greatly from the free market economy developed by the global capitalist economic system . This free market economic system tends to be the object of human being, so there is a very far gap between the community and the conglomerates, and this is the hallmark of the free market economy. But on the one hand the humanist economy does adopt some capitalist system, as well as individual ownership and also adopt the economic socialism in terms of togetherness. Keyword: humanistic economy, capitalistic economy and Pancasila economy